Perang Teknologi Amerika Serikat vs Tiongkok: Kebijakan Penolakan Teknologi 5G Huawei Tiongkok oleh Amerika Serikat - Bayuaji Pradipta Arinanda; Reni Windiani; Satwika Paramasatya (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The technology war between the United States and China is a struggle for dominance in core global technology, one of which is the 5G Internet Network. This has resulted in an escalation of conflict between the United States as a great power and China due to China's policy of rejecting Huawei's 5G internet technology. Therefore, this study aims to determine the factors and explain the reasons for the United States Government's rejection of China's 5G Huawei technology, and to find out how the United States' strategy is in China's hegemony efforts in the economic aspect with global technological mastery. The theory used by the author to analyze this research is the theory of offensive realism by using five assumptions according to Mearsheimer. The result of this study is that the United States as a Great Power wants to aggressively dominate China through Huawei's 5G Internet rejection policy. This is because the United States can increase its power over the control of 5G Internet Technology and strengthen China's economy, as well as ensure the strengthening of the United States' capability in the distribution of power in the international structure